Pertumbuhan dan Produksi Tanaman Kacang Kedelai Terhadap Pemberian Pupuk Kotoran Sapi dan Poc Kulit Pisang - Ariani Syahfitri Harahap; Maimunah Siregar; Fahrur Rozi Perangin Angin (JURNAL AGROPLASMA, 2023)
The purpose of this study was to determine the growth and production of soybean plants (glycine max L) with the response to cow dung and banana peel POC fertilizers and their interactions. This research method used a factorial randomized block design (RAK) consisting of 2 factors with 16 treatment combinations and 2 replications so that 32 research plots were needed. The first factor studied was the treatment of cow dung fertilizer with the symbol "S" consisting of S0 = 0 g/plant, S1 = 100 g/plant, S2 = 200 g/plant, and S3 = 300 g/plant. The second factor is giving POC banana peels with the symbol "K" consisting of K0 = 0 ml/liter of water/planting hole, K1= 200 ml/liter of water/planting hole, K2= 400 ml/liter of water/planting hole, and K3= 600ml/liter of water/planting hole. The parameters observed were plant height (cm), number of pods per sample (fruit), production per sample (g), production per plot (g) and weight per 100 seeds. The results showed that the application of cow dung fertilizer and banana peel POC had a significant effect on plant height (cm), but had no significant effect on the parameters of Number of Pods per Sample (fruit), production per sample (g), production per plot (g) and weight per 100 seeds. Keywords: Cow Manure, POC Banana Peel, Soybean